Storytelling para mejorar la enseñanza-aprendizaje de Estudios Sociales en el sexto grado de la Unidad Educativa “José Ángel Palacio”, Loja, periodo, 2023-2024 - Rengel Montesdeoca, Nataly Gabriela (2024)
Currently, it has become increasingly necessary to apply strategies to provide a better educational level, being storytelling a strategy that has been incorporated into education by including the contents in the form of meaningful and memorable stories. The general objective of this research is to determine the importance of storytelling in the teaching-learning of Social Studies in the sixth grade of the "José Ángel Palacio" Educational Unit. To achieve this objective, three specific objectives were developed: To identify the benefits of storytelling as a strategy to improve the teaching-learning of Social Studies, to describe the characteristics of the teaching-learning process of Social Studies, and to elaborate an alternative proposal of storytelling to improve the teaching-learning of Social Studies. The research was descriptive with a mixed approach and non-experimental design, in addition to this, the following methods were used: scientific, hermeneutic, analytical, synthetic, deductive, inductive and statistical; the techniques used were the observation sheet, the survey and the interview; being the questionnaire and the interview questions the instruments used for data collection. The population taken into consideration was the sixth grade of the "José Ángel Palacio" Educational Unit, by means of non-probabilistic sampling, where 14 students and 1 teacher were selected. The results of the research indicate that the storytelling strategy works as an educational alternative that improves the educational experience and the academic performance of students. Thus, it is concluded that the application of innovative strategies such as storytelling can contribute significantly to the acquisition of knowledge during the development of the teaching-learning process, which can be applied by both the teacher and the students.